Long‐Term Clinical Response to Medical Treatment, Behavioral Therapy, or Their Combination in Cats With Hyperesthesia Syndrome - Claudia Pauciulo; Stefania Uccheddu; Andrea Corda; Federica Biggio; Daniele Sebastian Corlazzoli; Marika Menchetti; Antonella Gallucci (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Hyperesthesia syndrome (HS) is a common yet poorly understood condition in cats, with hypothesized neurological and behavioral causes and limited data on outcomes and treatment. Objectives This study aimed to describe the clinical outcomes and the treatment response of 28 cats with HS, managed through various therapeutic strategies. Animals Clinical records of 28 cats with HS and minimum of 1‐year follow‐up were reviewed. Methods Retrospective, observational, descriptive study conducted on a case series of cats affected by HS. Sixteen cats (57%) received fluoxetine alone (Fluoxetine‐only), seven (25%) were managed with behavioral modification and gabapentin or fluoxetine (Fluoxetine/Gabapentin + Behavior) and five (18%) were treated with behavioral modification alone (Behavior‐only). Results An episode‐free period (EFP) ≥ 9 months was observed in 23 (82%) cats. Fifteen cats (94%) in the Fluoxetine‐only group experienced an EFP of ≥ 9 months. Moreover, they had a shorter time to recovery (median [IQR] = 8 [3.5–18] days) compared to the Fluoxetine/Gabapentin + Behavior and Behavior‐only groups (median [IQR] = 100 [90–210] and 60 [30–90] days, respectively). At the 1‐year follow‐up, 26 (93%) cats no longer had HS clinical signs and 14 (50%) were still under pharmacotherapy. Relapses were reported only in one case (4%). Conclusions Most of the cat's diagnosed with HS, and managed through various therapeutic strategies, experienced an EFP of more than 9 months and showed absence of clinical signs at 1 year follow‐up.